Utilization of Management Information Systems in Strategic Decision Making in the Human Resources Sector - Dharmawan, Ade Putra; Hamdani, Hamdani; Achmad, Gusti Noorlitaria (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
This study employs a systematic literature review and bibliometric analysis to examine trends, patterns, and conceptual developments in Human Resource Management Information Systems (HR-MIS). The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework was applied to ensure the literature review process was conducted systematically, transparently, and reproducibly. Selected articles met key inclusion criteria: published before April 16, 2026, written in English, and specifically discussing HR Management Information Systems. The Scopus database, an abstract and citation database of peer-reviewed literature, served as the primary data source for this literature review. A visual mapping analysis was performed using VOSviewer, software for constructing and visualizing bibliometric networks, to map citation networks, collaborations, and keyword co-occurrences, uncovering the intellectual structure and evolutionary trajectory of the human resource field. The findings indicate that the use of HR-MIS is strongly correlated with improved efficiency in strategic decision-making and resource allocation. The literature is divided into two primary clusters: strategic information governance and the operational impact on organizational behavior. By integrating bibliometric and systematic methodologies, this study successfully provides a comprehensive identification of key contributors, research trends, benefits, challenges, and future research agendas.